Towards Convergence in Social Protection Policies and Programmes - Ang, Alvin P (Archīum Ateneo, 2012)
Recognizing the relationship between macroeconomic, employment and social protection policies and their link to poverty reduction and inclusive development, some countries in developing Asia have pursued various initiatives towards greater policy coherence and institutional coordination in recent years. These varied efforts include better alignment of national poverty reduction programmes in Indonesia, the integration of employment targets into the national development plan in Nepal, convergence in social protection programmes in the Philippines and coordinated macroeconomic, employment and social protection policy responses to the global economic crisis of 2008–09 in Vietnam. Strengthening the coherence of policies and programmes is a complicated and arduous challenge. Various factors can be instrumental in the process, including strong political will and leadership, broad stakeholder engagement and support, rigorous research, information and analysis, and integrated monitoring and evaluation.